Dominant Discourse in Teachers' Perceptions about Self-Harm that is Performed by Female Students at Boarding School - Amalina Khairunnisa; Hani Yulindrasari; Suherman Suherman (International Journal Labs, 2022)
This study aims to determine the dominant discourse in the teacher's perception of self-harm that is carried out by female students in Boarding schools. The main characteristic in this study is the teacher (Ustadzah). This study uses a qualitative approach by using one of the paradigmatic discourse analysis methods. Data collection techniques using interview techniques. The research sample consisted of 3 ustadzah teaching at the Tangerang Islamic boarding school. The findings show that the dominant discourse on Ustadzah's perception of female students who practice self-harm is that they are innocent young women who do not have self-control and sufficient mental strength in dealing with problems. Female student who practice self- harm always begins with discomfort between herself and her family. Parents hope that sending their children to boarding schools can be a solution in overcoming this inconvenience. However, if the child is not equipped with sufficient physical and mental readiness, it will make the discomfort worse and end up in self-harm behavior. Handling of female students who practice self-harm is carried out in stages starting from giving special attention, monitoring developments and mediating with the family. And if the boarding school has made every effort to educate students involved in self-harm, but has not changed, the school returns the responsibility to educate parents and offers to seek treatment or therapy from a psychiatrist.